The effectiveness of schema therapy on rumination, perfectionism, and thought-action fusion of women suffering from obsessive-compulsive disorder - Khadem , Sedigheh; Fakhri , Mohammadkazem; Emadian , Seyedeh Olia (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of the present research was to determine the effectiveness of schema therapy on rumination, perfectionism, and thought-action fusion of women suffering from obsessive-compulsive disorder who are clients of counseling centers in Neka city. Method: It was a semi-experimental method with a pre-test and post-test design and follow-up with a control group and random assignment. The statistical population of this research included all women who referred to counseling centers in Neka city in the first three months of 2020. Purposive sampling and 30 women who obtained the highest score in the obsessive-practical research tool of Fua et al. (2002) were selected as a sample and then randomly assigned 15 to the schema therapy group and 15 to the group Certificates were assigned. The experimental group underwent schema therapy for 20 sessions based on the protocol of Luppino et al. (2018), while the control group did not receive any intervention. Also, the rumination questionnaire of Nalen-Hoeksma and Maro (1991), the identity perfectionism questionnaire of Hewitt and Felt (1991), and the thought-action fusion questionnaire of Shafran et al. (1996) were used in the pre-test, post-test and follow-up stages. Finally, the data were analyzed using ANOVA with repeated measures and Bonferroni's post hoc test. Results: The results showed that schema therapy on rumination (F=29.17, P